Key concepts - Sthapit, S.R.; Ramanatha Rao, V.; Lamers, Hugo A.H. (Routledge, 2016)
This chapter provides defintions on some key terms addressed by the book "Tropical fruit tree diversity: good practices for in-situ and on-farm conservation" (Sthapit et al. (eds.)). It is important to understand the wider context in which such practices take place, as some of them are relatively new concepts. Some well-accepted concepts are also included for clarity with respect to tropical fruit trees.